Avaliação objetiva de pavimentos pelo método IGG/DNIT: estudo de caso, rodovias de acesso ao porto do Arapari, a partir de Abaetetuba-PA - SARDINHA, Emilly de Melo (2025)
Highways play a crucial role in the Brazilian road system, being directly associated with the country's socioeconomic growth. To ensure comfort and efficiency in transportation, it is essential to maintain their service conditions adequately. In this context, the Pavement